Controversies in diagnostics of stress urinary incontinence in women - Wlaźlak, Edyta; Surkont, Grzegorz; Topczewska-Tylińska, Katarzyna; Stetkiewicz, Tomasz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2004)
Modern urogynecology gives us many diagnostic tools. Unfortunately their detailed clinical significance is yet to be evaluated. It is important to register objectively symptoms and to assess their real influence on patient’s quality of life. It is also important to evaluate subjective sense of women. Correct selection of mode of treatment depends on proper diagnostics. Nowadays there are few methods of stress urinary incontinence treatment with different degree of invasiveness. Their efficacy depends mainly on proper diagnostics.